(untitled) (CIPEEX, 2025)
When entering university, individuals face various challenges, changes, and conflicts, which can cause stress and psychological distress, leading to vulnerability and the risk of psychoactive substance and alcohol use and abuse during their academic years. The present study aims to identify and outline the profile of psychoactive substance users among students at a university in north-central Goiás. This is a descriptive cross-sectional field study with quantitative data analysis, conducted at the Evangelical University of Goiás – Ceres Campus. It is based on the “umbrella” method, with questionnaires for students aged 18 to 40 enrolled at the institution who agreed to participate in the study. The data obtained will be statistically analyzed using the Statistical Package for Social Science for Windows (SPSS) to survey the prevalence of psychoactive substance and alcohol use among university students, as well as symptoms of anxiety and depression. It will also contribute to a better understanding of the topic, identify consumption patterns and socioeconomic factors, and support preventive reflections on drug and alcohol use during the academic phase.